Magnesiation of Alkyl Fluorides Catalyzed by Rhodium–Aluminum Bimetallic Complexes - Fujii, Ikuya; Higo, Ryota; Semba, Kazuhiko; Nakao, Yoshiaki (Synlett, 2024)
Since the pioneering work by Grignard in 1900, organomagnesium reagents, the so-called Grignard reagents, have been indispensable in organic synthesis. Alkyl Grignard reagents are usually prepared from the corresponding alkyl iodides, bromides, or chlorides with Mg, whereas alkyl fluorides are not viable substrates under conventional conditions due to the high stability of the C–F bonds. We report that Al–Rh bimetallic complexes catalyze the magnesiation of C(sp3)–F bonds of alkyl fluorides using easy-to-handle Mg powder. The present conditions can accommodate primary, secondary, or tertiary alkyl fluorides to afford the corresponding alkylmagnesium reagents, which can be successfully converted into various functionalities.
Keywords: alkyl fluorides; organomagnesium compounds; Grignard reagents; aluminum catalysis; rhodium catalysis; C–F bond activation